Sinterização, caracterização e estudo das propriedades dielétricas de cerâmicas de TiO2 co-dopadas com íons Nb5+, Al3+ e Cr3+ - Lira, Stéfane Oliveira de (2020)
Dielectric ceramics free of lead presents great interest to the scientific community due its low toxicity or absence of it. In this work, ceramic materials of aluminum, chromium and niobium doped titanium dioxide (TiO2) Ti0,995[Nb1,33(AlxCr1-x)0,66]0,005O2 with x assuming the values of 1; 0,7; 0,5; 0,3; 0,1 in mols. Such materials were obtained through solid state reaction with uniaxial and isostatic cold pressing and sintering maximum temperature of 1500 °C. Structural, optics and electrics characterization were realized via Apparent density (rap), X-Ray diffraction (XRD), Fourier transform infrared (FTIR), Ultraviolet–visible spectroscopy (UV-Vis), Raman spectroscopy and Dielectric permittivity and Impedance spectroscopy. These caracterizations indicated the formation of the tetragonal rutile phase with no spurious phases and all the samples presented 97 to 99% densification. FTIR, UV-Vis and Raman measurements confirmed the tetragonal rutile crystalline phase by means of characteristic vibrational bands, in addition to allowing the observation of the increase in defects and the reduction of the band gap with doping. The dielectric permittivity and impedance measurements prove the presence of Colossal permittivity effect (e’ ~ 106) for all the samples, increasing dielectric constant with doping. The samples high permittivity was atrtibuted to the presence of electron confinement in complex clusters of defects and the presence of potencial barriers in grain boundary.